Proton MRS and quantitative MRI assessment of the short term neurological response to antiretroviral therapy in AIDS. Issue 4 (1st October 1997) - Wilkinson, Iain D; Lunn, Sarah; Miszkiel, Katherine A; Miller, Robert F; Paley, Martyn N J; Williams, Ian; Chinn, Roger J S; Hall-Craggs, Margaret A; Newman, Stanton P; Kendall, Brian E; Harrison, Michael J G
Abstract : OBJECTIVE: To investigate MRI and proton spectroscopy changes in five patients with HIV associated dementia complex (HADC) treated with antiretroviral therapy. METHODS: Three markers were evaluated: (1) CSF/intracranial volume ratio; (2) T2 weighted signal ratio between parieto-occipital white and subcortical grey matter; and (3) metabolite ratios from long echo time (TE=135 ms) single voxel proton spectra of parieto-occipital white matter. RESULTS: Spectroscopic changes indicated initial increases in N-acetyl/(N-acetyl + choline + creatine) ratio (NA/(NA+ Cho+Cr)) and progression of atrophy after initiation of antiretroviral therapy in four of five patients. When the neurological status of the patients subsequently deteriorated (two of five patients), the NA/(NA+Cho+Cr) ratio also declined. CONCLUSIONS: spectroscopic changes mirror reversible neuronal dysfunction. These objective, non-invasive techniques may be used for monitoring the neurological effects of antiretroviral drug therapy in patients with HADC.